The Effect of Deferred Tax Expenses on Earnings Management - Purnamasari, Dyah; Abdul Hadi, Dudi; Sukmawati, Fitri (International Journal of Psychosocial Rehabilitation, 2020)
This study is entitled "The Effect of Deferred Tax Expenses on Earnings Management." Companies always look for loopholes to prevent small tax profits from being paid and increase profits to attract investors. This can be used as information in financial statements to look good. This study aims to analyze the effect of deferred tax expenses on earnings management (Study on Automotive Sub-Sector Manufacturing Companies listed on the Stock Exchange for the period 2014-2018). The data used in this study comes from audited financial statements at 7 companies listed on the Indonesia Stock Exchange for the period 2014-2018. The research method used in this study is a descriptive research method with a quantitative approach. The sampling technique used is nonprobability sampling; samples are taken by the purposive sampling technique.